Clinical, immune cell, and genetic features predicting survival and long-term response to first-line chemo-immunotherapy treatment for non-small cell lung cancer - Liling Huang; Haohua Zhu; Liyuan Dai; Yu Feng; Xinrui Chen; Zucheng Xie; Xingsheng Hu; Yutao Liu; Xuezhi Hao; Lin Lin; Hongyu Wang; Shengyu Zhou; et al. (Cancer Immunology, Immunotherapy)
Abstract Introduction Chemo-immunotherapy has become a standard of care for the first-line treatment of non-small cell lung cancer (NSCLC), but currently still lacks reliable markers to predict therapeutic efficacy and long-term response (LTR). Methods In this study, we retrospectively summarized the survival outcome of 319 patients with locally advanced or metastatic NSCLC who received anti-programmed cell death protein-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) based therapy from January 1st, 2018 to February 28th, 2022 at the Cancer Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College. Then a comprehensive analysis of the association of LTR or survival outcomes with various characteristics including clinical parameters, peripheral blood lymphocyte subsets and common gene mutations in 167 NSCLC patients who received first-line anti-PD-1 plus chemotherapy treatment was conducted. LTR was defined as progression-free survival (PFS) exceeding 24 months, while non-responders had a PFS of less than 6 months. Results With a median follow-up time of 32.1 months (95% confidence interval [CI] 29.2–38.0), the median overall survival (OS) was 29.9 months (95% CI 23.6–37.5) in locally advanced or metastatic NSCLC receiving anti-PD-1/PD-L1 based treatment. Among 167 patients who received the first-line chemo-immunotherapy, 25.1% (n = 42) achieved LTR. Independent baseline predictors of LTR included age < 65 years (odds ratio [OR] = 3.22, p = 0.024), overweight or obesity (body mass index [BMI] ≥ 24 kg/m2, OR = 3.26, p = 0.020), and a C-reactive protein/albumin ratio (CAR) score < 0.07 (OR = 9.94, p = 0.039). In multivariate cox analysis, both patients with higher CAR scores of ≥ 0.07 (hazard ratio [HR] = 2.83, p = 0.016) and those who were underweight (BMI < 18.5 kg/m2) (HR = 4.52, p = 0.005) were observed with significantly shorter OS. A peripheral B cell percentage ≥ 14.5% was more prevalent among LTR patients (OR = 9.23, p = 0.045) after adjusting for age, BMI and TNM stage. Additionally, the presence of TP53 mutation (16/66) was associated with non-response to first-line chemo-immunotherapy (p = 0.048) and shorter PFS (p = 0.028) and OS (p = 0.023) outcomes in univariate analysis. Conclusions This study provides some new insights into the features and predictors significantly associated with LTR and survival in NSCLC patient receiving first-line treatment of anti-PD-1 plus chemotherapy. Those whose age < 65 years, overweight or obesity, or has a baseline CAR score < 0.07 are more likely to achieve optimal benefit from the first-line treatment of chemo-immunotherapy.